Preparation method and application of zinc-manganese bimetal organic framework derived composite nano-enzyme

By preparing nitrogen-doped porous carbon-supported zinc-manganese oxide composites, the problem of difficult control of nano size and insufficient catalytic activity in the prior art is solved, and a multifunctional anti-tumor nanomaterial with good biosafety is achieved.

CN119528122AInactive Publication Date: 2025-02-28CHANGZHOU UNIV
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411701643.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing MOF and its derived composite materials are difficult to control in the nanometer size, lack of catalytic activity, and contain heavy metal elements that are not essential to the human body, which poses biosafety risks.

Method used

By preparing nitrogen-doped porous carbon-supported zinc-manganese oxide composite materials, the preparation method of zinc-manganese bimetallic organic framework derived composite nanoenzymes is used to control the calcination temperature and time to adjust the structure and properties of the material.

Benefits of technology

The prepared nanomaterials have the activities of peroxidase-like, glutathione-like peroxidase-like, which can effectively inhibit the growth of tumor cells and contain only essential elements of the human body, which has good biosafety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005153457990000011
    Figure HDA0005153457990000011
  • Figure HDA0005153457990000012
    Figure HDA0005153457990000012
  • Figure HDA0005153457990000021
    Figure HDA0005153457990000021
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a zinc-manganese bimetal organic framework derived composite nano-enzyme, and belongs to the technical field of nano-materials. Zinc-manganese bimetal organic framework nanoparticles prepared by reacting ZIF-8 with manganese (III) acetylacetonate are used as a template, and are calcined at different temperatures in a tubular furnace to obtain zinc-manganese bimetal organic framework derivative composite nano-enzymes with different morphologies. The nano enzyme has peroxidase-like activity, glutathione peroxidase-like activity and catalase-like activity, and has a wide application prospect in anti-tumor treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nanomaterials, and specifically relates to a preparation method and application of a zinc-manganese bimetallic organic framework-derived composite nanozyme. Background Art

[0002] Metal-organic frameworks (MOFs) are a class of three-dimensional porous materials composed of metal ions and organic ligands connected by coordination bonds. Their channel structure facilitates rapid mass transfer, while their unique pore size facilitates the adsorption, loading, and separation of target substances, making them excellent carriers for drug delivery.

[0003] Typically, the metal nodes in MOF crystals are fully coordinated, which can impart catalytic activity to the MOF, but the catalytic active sites are rarely fully exposed. After derivatization, MOFs typically retain the porous structure of the original framework, resulting in a high specific surface area. This high specific surface area enables the material to perform well in applications such as catalysis and adsorption. During the derivatization process, the organic ligands in the MOF are partially removed or converted, but the metal nodes and some organic structures may recombine to form a new porous structure, which also helps to improve the material's reactivity and adsorption capacity. The metal-carbon complexes or metal oxide-carbon complexes formed by the metal ions and carbon in the MOF often exhibit superior catalytic performance and stability compared to the MOF precursors. By selecting different MOF precursors and controlling pyrolysis conditions (such as temperature and atmosphere), the structure and properties of the derived materials can be tuned. This tunability makes MOF-derived materials widely applicable in different applications.

[0004] MOF-derived composite materials have been widely used in biosensing, electrochemical energy conversion and storage, and other fields. These materials can be designed to achieve different enzyme activity centers, such as peroxidase, catalase, superoxide dismutase, and glutathione peroxidase, among other anti-tumor enzyme activities. Size is a key factor in designing nanoparticles with optimal in vivo transport behavior for effective targeting and clearance. It is generally believed that nanoparticles under 200 nm are more likely to penetrate intestinal mucus ( ACS Nano 2023, 17, 21, 20825–20849 Currently, MOFs and their derived composite materials are often large in size, making them difficult to control. Furthermore, the activity of nanozymes derived from most MOFs and their derived composite materials still needs to be improved. MOFs and their derived composite materials with good catalytic activity often contain non-essential elements such as nickel, cobalt, or other heavy metals, posing a biosafety risk. Summary of the Invention

[0005] To address the shortcomings of the existing technology, the present invention provides a method for preparing and applying a zinc-manganese bimetallic organic framework-derived composite nanozyme. This method can produce a nitrogen-doped porous carbon-supported zinc-manganese oxide composite material that exhibits enzyme-like activities, such as peroxidase- and glutathione peroxidase-like activities, and can inhibit tumor cell growth.

[0006] The present invention first provides a method for preparing a zinc-manganese bimetallic organic framework-derived composite nanozyme, comprising the following steps: (1) Dissolve 2-methylimidazole in a solvent and stir at room temperature for 5 to 10 minutes to obtain a 2-methylimidazole solution; dissolve a water-soluble zinc salt in a solvent and dissolve it by ultrasonication to obtain a zinc salt solution; add the zinc salt solution dropwise to the above 2-methylimidazole solution and stir rapidly to react for 5 to 10 minutes; after the reaction is completed, wash with methanol for 1 to 3 times and dry in a constant temperature forced air drying oven to obtain ZIF-8.

[0007] The solvent is methanol, N,N-dimethylformamide (DMF), water or a mixed solvent thereof, preferably methanol.

[0008] The concentration of the 2-methylimidazole solution is 1-10 mol / L, preferably 2.5-5 mol / L, more preferably 3-3.5 mol / L.

[0009] The concentration of the water-soluble zinc salt in the zinc salt solution is 0.2-1 mol / L, preferably 0.4-0.671 mol / L, and more preferably 0.5 mol / L.

[0010] Wherein, the molar ratio of 2-methylimidazole to zinc nitrate hexahydrate is 1: 0.01 to 0.02, preferably 1: 0.014 to 0.015.

[0011] The water-soluble zinc salt includes, but is not limited to, one or more of zinc nitrate, zinc nitrate hexahydrate, zinc sulfate, zinc sulfate hexahydrate, zinc acetate, zinc acetate dihydrate, zinc chloride, etc.; preferably, zinc nitrate hexahydrate.

[0012] Among them, the centrifugal rate is 12000r / min and the centrifugal time is 10min.

[0013] The drying temperature of the constant temperature blast drying oven is 55°C and the drying time is 4 to 6 hours.

[0014] (2) The prepared ZIF-8 and manganese (III) acetylacetonate were dissolved in a solvent and placed in a constant temperature forced air oven for 24 h. The mixture was centrifuged and washed with methanol 1-3 times. The mixture was then immersed in methanol for 3 days, and fresh methanol was replaced by centrifugation every 24 h. After immersion for 3 days, the mixture was centrifuged and dried in a constant temperature forced air oven to obtain manganese-doped zinc-manganese bimetallic organic framework nanoparticles.

[0015] The molar ratio of ZIF-8 to manganese (III) acetylacetonate is 1:1~5.

[0016] The solvent is methanol, and the concentration of manganese (III) acetylacetonate dissolved in the solvent is 0.05-0.1 mol / L.

[0017] The reaction temperature is 50-60°C, preferably 55°C.

[0018] The centrifugal speed was 12000 r / min and the centrifugal time was 10 min.

[0019] The drying temperature of the constant temperature blast drying oven is 55°C and the drying time is 4 to 6 hours.

[0020] (3) The prepared brown solid powder of zinc-manganese bimetallic organic framework nanoparticles was spread evenly in a porcelain boat, and sufficient N2 was maintained. The porcelain boat was placed in a tube furnace for calcination. After naturally cooling to room temperature, a black-brown solid powder was obtained, and a zinc-manganese bimetallic organic framework-derived composite nanozyme material was obtained.

[0021] The calcination conditions are as follows: a tube furnace heating rate of 0.5-5°C / min, a calcination temperature of 200-500°C, and a holding time of 30-120 min. Preferably, the calcination conditions are as follows: a tube furnace heating rate of 3°C / min, a calcination temperature of 250-450°C, and a calcination time of 60 min. More preferably, the calcination conditions are as follows: a tube furnace heating rate of 3°C / min, a calcination temperature of 350-450°C, and a calcination time of 60 min.

[0022] The zinc-manganese bimetallic organic framework-derived composite nanoenzyme prepared using the above method has a diameter of less than 100 nm. This nanomaterial was dissolved in an ultrapure aqueous solution and tested for enzyme activity. The results showed that it exhibited enzyme-like activities, including peroxidase-, glutathione peroxidase-, and catalase-like activities.

[0023] In vitro cell experiments showed that the prepared zinc-manganese bimetallic organic framework-derived nanozyme material can effectively inhibit cell growth after incubation with mouse breast cancer cells (4T1), and has no obvious effect on mouse embryonic fibroblasts (3T3 cells), showing excellent anti-tumor activity and biosafety, suggesting that the zinc-manganese bimetallic organic framework-derived nanozyme prepared by the present invention can be used as one of the active ingredients in the preparation of anti-tumor drugs.

[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention provides a method for preparing a zinc-manganese bimetallic organic framework-derived composite nanozyme. During synthesis, only essential elements for the human body, such as manganese, zinc, nitrogen, carbon, and oxygen, are introduced, thus avoiding metabolic toxicity. Furthermore, the preparation method is simple and environmentally friendly. By controlling the precursor reaction time, the nanozyme is uniformly sized and less than 100 nm, meeting the nanomaterial size requirements for anti-tumor therapeutics.

[0025] (2) The zinc-manganese bimetallic organic framework-derived composite nanozyme prepared by the present invention has excellent catalytic activity and stability due to the porous carbon material as the substrate, and exhibits multiple types of enzyme activities. It can catalyze the catalytic conversion of hydrogen peroxide and glutathione overexpressed in tumor cells, and the material composition can be controlled by calcination temperature, thereby regulating the type and activity of enzyme-like activities.

[0026] (3) The calcination modification method of the present invention is simple, easy to operate, and low-cost. Anti-tumor nanomaterials with different functionalities can be achieved by controlling experimental parameters such as calcination temperature and calcination time, which expands the preparation strategy and application scope of MOF-derived carbon composite nanomaterials and provides new ideas for the design of multifunctional anti-tumor nanosystems. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope image of the ZIF-8 nanoparticles prepared in Example 1.

[0028] Figure 2 This is a transmission electron microscopy image of ZIF-8 nanoparticles prepared in Example 1.

[0029] Figure 3 This is a scanning electron microscope image of ZIF-8-Mn nanoparticles prepared in Example 2.

[0030] Figure 4 This is a transmission electron microscope image of ZIF-8-Mn nanoparticles prepared in Example 2.

[0031] Figure 5 X-ray diffraction patterns of ZIF-8 and ZIF-8 and Mn-ZIF-8 nanomaterials prepared by the present invention; Figure 6 This is a scanning electron microscope image of the ZM-250 nanomaterial prepared in the present invention.

[0032] Figure 7 This is a scanning electron microscope image of the ZM-350 nanomaterial prepared in the present invention.

[0033] Figure 8 This is a scanning electron microscope image of the ZM-450 nanomaterial prepared in the present invention.

[0034] Figure 9These are the X-ray diffraction patterns of the ZM-250, ZM-350, and ZM-450 nanomaterials prepared in the present invention.

[0035] Figure 10 These are peroxidase activity detection spectra of the samples prepared in Examples 2-5 respectively.

[0036] Figure 11 These are spectra of glutathione oxidase activity detection of the samples prepared in Examples 2-5 respectively.

[0037] Figure 12 Catalase activity evaluation diagram of samples prepared in Examples 2-5 Figure 13 This is a graph showing the cytotoxic activity test of ZM-350 prepared in Example 4 on 4T1 cells.

[0038] Figure 14 This is a graph showing the cytotoxic activity test of ZM-350 prepared in Example 4 on 3T3 cells. DETAILED DESCRIPTION

[0039] The technical solutions of the present invention are described in detail below with reference to the embodiments, but the protection scope of the present invention is not limited to the following embodiments. Example 1

[0040] Dissolve 0.117 g of zinc nitrate hexahydrate in 0.8 mL of methanol to obtain Solution A, and dissolve 2.27 g of 2-methylimidazole in 8 mL of methanol to obtain Solution B. Add Solution A dropwise to Solution B and stir at room temperature for 10 minutes. After completion of the reaction, centrifuge (12,000 rpm), discard the supernatant, and collect the precipitate. Wash the precipitate three times with 10 mL of methanol and dry it to obtain a white powder, which is the ZIF-8 nanomaterial.

[0041] From the attached Figure 1 、 2 Scanning electron microscopy and transmission electron microscopy images show that the MOF is a polyhedral nanoparticle morphology with a particle size less than 100nm and uniform. Figure 5 It can be seen from the XRD spectrum of the sample that it matches the ZIF-8 reported in the literature. Example 2

[0042] Disperse or dissolve 0.026g of the prepared ZIF-8 and 0.12g of manganese(III) acetylacetonate in 4mL of methanol in a constant-temperature, forced-air drying oven. Allow to react at 55°C for 24 hours. Centrifuge and wash with methanol one to three times. Soak in methanol for three days, replacing fresh methanol every 24 hours. After soaking for three days, centrifuge and dry in a constant-temperature, forced-air drying oven to obtain a brown solid powder, the zinc-manganese bimetallic organic framework nanomaterial.

[0043] From the attached Figure 3 、 4 The scanning electron microscope and transmission electron microscope images show that the morphology of the MOF material is consistent with that of Example 1, suggesting that Mn ions may be adsorbed inside the ZIF-8 material. Figure 5 It can be seen from the XRD spectrum of the sample that the sample is consistent with the ZIF-8 prepared in Example 1, indicating that the replacement of Mn ions into ZIF-8 does not change its crystal form. Example 3

[0044] The brown solid powder prepared according to the method of Example 2 was spread evenly in a porcelain boat, and sufficient N2 was maintained. The porcelain boat was placed in a tube furnace and calcined at a heating rate of 3°C / min. It was calcined at 250°C for 1 hour. After naturally cooling to room temperature, the black-brown product was collected as the zinc-manganese bimetallic organic framework nanozyme material ZM-250.

[0045] From the attached Figure 6 It can be seen from the figure that the morphology of ZM-250 is slightly different from that of Mn-ZIF-8. Figure 9 It can be seen from the XRD spectrum of ZM-250 that the diffraction peak of ZIF-8 in the XRD of ZM-250 changes little. Due to the low calcination temperature, its morphology changes little and no derivative substances appear. This sample can be considered as the Mn-ZIF-8 prepared in Example 2, which removes the low-boiling point substances in its MOF structure during calcination. Example 4

[0046] The brown solid powder prepared according to the method of Example 2 was spread evenly in a porcelain boat, and sufficient N2 was maintained. The porcelain boat was placed in a tube furnace and calcined at a heating rate of 3°C / min. It was calcined at 350°C for 1 hour. After naturally cooling to room temperature, the black-brown product was collected as the zinc-manganese bimetallic organic framework nanozyme material ZM-350.

[0047] Attachment Figure 7 It can be seen that the morphology of ZM-350 has changed compared with Mn-ZIF-8, becoming a granular MOF-derived composite material with smaller and more uniform particle size. Figure 9 It can be seen from the XRD spectrum of the sample that there are three groups of diffraction peaks, namely ZIF-8 and ZnO / MnO, which indicates that the zinc-manganese bimetallic organic framework prepared in Example 4 retains the MOF structure of ZIF-8, while the zinc ions and manganese ions therein are converted into ZnO / MnO with anti-tumor activity under calcination. Example 5

[0048] The prepared brown solid powder was spread evenly in a porcelain boat, and sufficient N2 was maintained. The porcelain boat was placed in a tube furnace and calcined at a heating rate of 3°C / min. It was calcined at 450°C for 1 hour. After naturally cooling to room temperature, the black-brown product was collected as the zinc-manganese bimetallic organic framework nanozyme material ZM-450.

[0049] Attachment Figure 8 It can be seen that the morphology of ZM-450 is significantly different from that of Mn-ZIF-8. Based on Example 5, obvious oxide particles are derived. Figure 9 It can be seen from the XRD spectrum of the sample that due to the high calcination temperature, the diffraction peak of ZIF-8 in the product XRD disappears, indicating that the ZIF-8 structure collapses and only the diffraction peak of ZnO / MnO appears. This sample can be considered to be a nitrogen-doped carbon-supported ZnO / MnO composite material formed after calcining Mn-ZIF-8 prepared in Example 2. Example 6

[0050] The zinc-manganese bimetallic organic framework Mn-ZIF-8 prepared according to Example 2 and the zinc-manganese bimetallic organic framework nanozyme materials prepared at different calcination temperatures according to Examples 3-5 were subjected to peroxidase (POD) activity detection.

[0051] Prepare 1 mg / mL sample solution with ultrapure water, take appropriate amount and mix with 3,3',5,5'-tetramethylbenzidine (TMB) and hydrogen peroxide (H2O2) in citric acid-sodium citrate buffer at pH 4.0 to make the final sample, TMB, and H2O2 1 mM. Place the mixed solution at 37 o The reaction was allowed to stand at a constant temperature of 500°C in the dark for 6 minutes. The product was then measured in a UV spectrophotometer at wavelengths ranging from 500 nm to 800 nm, comparing the changes in the characteristic peaks of TMB oxidation by each product. The intensity of the absorption peak at 652 nm indicated the yield of hydroxyl radicals, i.e., the peroxidase activity.

[0052] As attached Figure 10 As shown in the figure, compared with Mn-ZIF-8, the absorption peak positions of ZM-250 and ZM-450 changed slightly after reaction, while the absorption peak position of ZM-350 increased most significantly after reaction, indicating that ZM-350 has the best POD activity. Example 7

[0053] The Mn-based metal organic framework Mn-ZIF-8 prepared according to Example 2 and the zinc-manganese bimetallic organic framework nanozyme materials prepared at different calcination temperatures according to Examples 3-5 were subjected to glutathione peroxidase (GPX) activity detection.

[0054] Prepare 1 mg / mL sample solution with ultrapure water, take appropriate amount and mix with glutathione solution in PBS buffer, so that the final concentration of sample and glutathione is 30 μg / mL and 1 mM. o The reaction was allowed to proceed in a dark shaking incubator at 4°C. After 1 hour, DTNB solution was added to each sample and the absorbance curve was measured using a UV spectrophotometer in the wavelength range of 300 nm to 500 nm. The decrease in the absorbance peak at 412 nm compared to the control group indicated the glutathione consumption capacity, i.e., the glutathione peroxidase activity.

[0055] As attached Figure 11 As shown in the figure, the glutathione peroxidase activity of Mn-ZIF-8 is the lowest under the same reaction time. With the increase of the calcination temperature of the sample, the glutathione peroxidase activity of the product becomes stronger and stronger, specifically ZM-450>ZM-350>ZM-250>Mn-ZIF-8. Among them, the absorption peak position of ZM-450 after reaction is the lowest, which proves its highest glutathione peroxidase-like activity. Example 8

[0056] The Mn-based metal organic framework Mn-ZIF-8 prepared according to Example 2 and the zinc-manganese bimetallic organic framework nanozyme materials prepared at different calcination temperatures according to Examples 3-5 were subjected to catalase (CAT) activity detection.

[0057] The study of catalase-like activity was measured using a dissolved oxygen meter. 5.37 mL of PBS buffer (0.2 M, pH=7.6) and 0.6 mL of H2O2 (1 mM) were added to a 10 mL vial. 0.03 mL of a 1 mg / mL sample solution was prepared with ultrapure water and added to the vial (final concentration was 20 μg / mL). The dissolved oxygen probe was then immediately inserted to read the data changes within 300 s (every 30 s). The zinc-manganese bimetallic organic framework nanozyme catalyzes the decomposition of hydrogen peroxide to produce oxygen, increasing the dissolved oxygen level in the solution. The results are shown in Figure 2. Figure 12 As shown in the figure, compared with uncalcined Mn-ZIF-8, the nanozymes produced at the three calcination temperatures all exhibited certain CAT activity, with ZM-450 having the strongest activity, followed by ZM-350, and ZM-250 having the weakest. This indicates that the catalase-like activity of the product increases with the increase in the calcination temperature of Mn-ZIF-8. Example 9

[0058] The zinc-manganese bimetallic organic framework-derived composite nanoenzyme material ZM-350 prepared in Example 4 was subjected to cytotoxicity testing.

[0059] 4T1 and 3T3 cells were digested, counted, and 10 4The number of cells per well was seeded into a 96-well plate and cultured overnight in a 37°C carbon dioxide (5%) incubator. The samples were prepared into different concentrations using DMEM medium and then added to the well plate. They were then placed in a constant temperature carbon dioxide incubator and incubated for 24 hours. 20 mL of CCK-8 solution was added to each well and incubated in the incubator for 1 hour. After shaking on a shaker, the absorbance value of each well at 450 nm was measured using a microplate reader. Figure 13 As shown in the figure, ZM-350 is cytotoxic after incubation and can effectively kill 4T1 cells. A concentration of 50 μg / mL can reduce the cell survival rate by 40.1%. Figure 14 As shown, ZM-350 had no obvious cytotoxicity after incubation with 3T3 cells and had little effect on the survival rate of 3T3 cells.

[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing a zinc-manganese bimetallic organic framework-derived composite nanozyme, characterized in that: The following steps are involved: (1) dissolving 2-methylimidazole in a solvent, and stirring at room temperature for 5 to 10 minutes to obtain a 2-methylimidazole solution; dissolving a water-soluble zinc salt in a solvent to obtain a zinc salt solution; dropping the zinc salt solution into the 2-methylimidazole solution, and rapidly stirring at room temperature for reaction for 5 to 10 minutes; after the reaction is completed, washing and drying to obtain ZIF-8; (2) dissolving the prepared ZIF-8 and manganese (III) acetylacetonate in a solvent and placing the mixture in a constant temperature forced air oven for 24 hours, centrifuging, washing, and drying to obtain zinc-manganese bimetallic organic framework nanoparticles; (3) The prepared zinc-manganese bimetallic organic framework nanoparticles are calcined in a nitrogen atmosphere to obtain a zinc-manganese bimetallic organic framework-derived composite nanozyme.

2. The method for preparing the zinc-manganese bimetallic organic framework-derived composite nanozyme according to claim 1, characterized in that: The molar ratio of 2-methylimidazole to zinc nitrate hexahydrate in step (1) is 1: 0.01 to 0.

02.

3. The method for preparing the zinc-manganese bimetallic organic framework-derived composite nanozyme according to claim 1, characterized in that: The water-soluble zinc salt is one or more of zinc nitrate, zinc nitrate hexahydrate, zinc sulfate, zinc sulfate hexahydrate, zinc acetate, zinc acetate dihydrate, and zinc chloride; the solvent is one or more of methanol, N,N-dimethylformamide, and water.

4. The method for preparing the zinc-manganese bimetallic organic framework-derived composite nanozyme according to claim 1, characterized in that: The concentration of the 2-methylimidazole solution is 1-10 mol / L, and the concentration of the water-soluble zinc salt in the zinc salt solution is 0.2-1 mol / L.

5. The method for preparing the zinc-manganese bimetallic organic framework-derived composite nanozyme according to claim 1, characterized in that: The molar ratio of ZIF-8 to manganese (III) acetylacetonate in step (2) is 1:1 to 5.

6. The method for preparing the zinc-manganese bimetallic organic framework-derived composite nanozyme according to claim 1, characterized in that: The concentration of manganese (III) acetylacetonate in the solvent in step (2) is 0.05-0.1 mol / L.

7. The method for preparing the zinc-manganese bimetallic organic framework-derived composite nanozyme according to claim 1, characterized in that: The static reaction temperature in step (2) is 50-60°C.

8. The method for preparing the zinc-manganese bimetallic organic framework-derived composite nanozyme according to claim 1, characterized in that: The calcination conditions in step (3) are as follows: the heating rate of the tubular furnace is 0.5-5°C / min, the calcination temperature is 200-500°C, and the temperature is maintained for 30-120 min.

9. The method for preparing the zinc-manganese bimetallic organic framework-derived composite nanozyme according to claim 1, characterized in that: The diameter of the zinc-manganese bimetallic organic framework-derived composite nanozyme is less than 100 nm; and / or, the zinc-manganese bimetallic organic framework-derived composite nanozyme has peroxidase-like, glutathione peroxidase-like and catalase-like activities.

10. Use of the zinc-manganese bimetallic organic framework-derived composite nanozyme prepared by the method according to any one of claims 1 to 9 in the preparation of anti-tumor drugs.

Citation Information

Cited By

  • Zn-Mn bimetallic ZIF material and preparation method and application thereof

    CN120518879A

  • Manganese-cerium synergistically doped metal organic framework nano material, preparation method and application

    CN121015905A

  • Preparation method of Zn-based bimetal MOFs (Metal-Organic Frameworks) material and application of Zn-based bimetal MOFs material as medical drug-loading material

    CN121949817A

  • Application of ABC transporter substrate binding protein in preparation of vaccine for resisting arcanobacterium pyogenes

    CN122251562A

  • Zinc-based nano-enzyme as well as preparation method and application thereof

    CN122351035A